How long do external capital constraints matter? A study based on Swiss data for the start-up cohort 1996 - 97 - Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2009)
Start-ups mostly have only limited internal financing. Post-entry performance should thus strongly depend on the availability of new external capital. In this study we analyze the impact of financial constraints on the performance of Swiss start-ups. Since we use cohort data, we have for some start-ups data at different points in time. This allows us to analyze whether the effect of the availability of external capital on firm performance changes with increasing age of the firms. To measure the impact of external capital as a whole, we include separate indicators for debt and venture capital constraints. Using different performance measures, we find that debt constraints are not only a problem of the first years. While the negative impact of debt constraints on firm survival disappears with increasing age of the firms, profit is persistently negative affected by debt constraints. Debt constraints, however, do not impact employment growth of the firms, not even in the first years. The availability of venture capital is of lower relevance for the post-entry performance. Surviving and growth of the start-ups is not affected by venture capital constraints. However, firms with limited access to venture capital persistently have problems to attain profit break-even.
Keywords: M13; L25; G32; 330; start-ups; performance; financial constraints; firm age; Unternehmensgründung; Kapitalbedarf; Unternehmensentwicklung; Verschuldungsrestriktion; Schweiz